Eskatologi: Doktrin Akhir Zaman - Aprilia Pasca; Amanda gresella putri (Kampus Akademik Publiser, 2025)
This study aims to theologically analyze the doctrine of eschatology, the teaching about the end times, from the perspective of the Bible and systematic theology in the Christian church. Eschatology is a very important part of the Christian faith, because it affirms God's plan that will be realized through the second coming of Jesus Christ. This study uses a library study method by studying various theological sources such as the scriptures, the works of the church fathers, and the thoughts of modern theologians. The results obtained show that eschatology is not only related to the end of the world, but also includes new hope, the renewal of creation, and the fulfillment of God's promise of salvation. This teaching has deep spiritual and ethical meaning, because it invites Christians to live in readiness, obedience, and loyalty to God. By understanding this doctrine, believers are reminded that life on earth is temporary, while the true hope is eternal life with Christ. Eschatology also plays a role in shaping the moral and social responsibility of the church, so that it can be a witness to God's love and truth in the midst of the world.